Comparative performance of radiata pine genotypes with pasture understories - Peri, Pablo Luis (2003)
This paper presents results from a silvopastoral experiment that investigated interactions between four different pasture types and growth and form of five different ‘genotypes’ of radiata pine (four micro-propagated clones and one seedling lot). The five radiata pine tree ‘genotypes’ tested in this experiment displayed differences in growth and form 10 years after planting. However, there were no statistically significant interactions between tree genotype and understorey effects. The two best ‘genotypes’ were superior in nearly all respects (growth, branch size and stem form), on all pasture types. These results concur with other research results that indicate that the best radiata pine genotypes will perform consistently well across a range of environments in New Zealand.